Possible Therapeutics for Pseudomyxoma Peritonei: A Rare, Lethal, and the Least Investigated Disease - Nazmeen, Aarifa (Journal of Coloproctology, 2023)
Pseudomyxoma peritonei (PMP) refers to a growth disorder characterized by glycoprotein neoplasm in the peritoneum, where mucin oversecretion occurs. The tumors of the appendix region are well associated with PMP; however, ovarian, colon, stomach, pancreas, and urachus tumors have also been linked to PMP. Other mucinous tumors in the pelvis, paracolic gutters, greater omentum, retrohepatic space, and Treitz ligament can be the reason for PMP. Despite being rare and having a slow growth rate, PMP can be lethal without treatment. It is treated with neoadjuvant chemotherapy with the option of cytoreductive surgery and intraperitoneal chemotherapy. In the current study, we hypothesize that there may be novel gentle ways to inhibit or eliminate the mucin. Dr. David Morris has used mucolytics—such as bromelain and N-acetyl cysteine to solubilize mucin. In the present review, we aimed to study the regulation of mucin expression by promoter methylation, and drugs that can inhibit mucin, such as boldine, amiloride, naltrexone, dexamethasone, and retinoid acid receptors antagonist. This review also explored some possible pathways, such as inhibition of Na + , Ca2+ channels and induction of DNA methyltransferase along with inhibition of ten-eleven translocation enzymes, which can be good targets to control mucin. Mucins are strong adhesive molecules that play great roles in clinging to cells or cell to cell. Besides, they have been greatly involved in metastasis and also act as disease markers for cancers. Diagnostic markers may have exclusive roles in disease initiation and progression. Therefore, the present review explores various drugs to control and target mucin in various diseases, specifically cancers.
Keywords: pseudomyxoma peritonei; retinoid; boldine; therapy; N-acetyl cysteine